JAGGED1 IS NECESSARY FOR POSTNATAL AND ADULT NEUROGENESIS IN THE DENTATE GYRUS - Lavado, Alfonso (2014)
Understanding the mechanisms that control the maintenance of neural stem cells is crucial for the study of neurogenesis. In the brain, granule cell neurogenesis occurs during development and adulthood, and the generation of new neurons in the adult subgranular zone of the dentate gyrus contributes to learning. Notch signaling plays an important role during postnatal and adult subgranular zone neurogenesis, and it has been suggested as a potential candidate to couple cell proliferation with stem cell maintenance. Here we show that conditional inactivation of Jagged1 affects neural stem cell maintenance and proliferation during postnatal and adult neurogenesis of the subgranular zone. As a result, granule cell production is severely impaired. Our results provide additional support to the proposal that Notch/Jagged1 activity is required for neural stem cell maintenance during granule cell neurogenesis and suggest a link between maintenance and proliferation of these cells during the early stages of neurogenesis.